Filsafat Sejarah Dalam Perspektif Santo Agustinus - Putri, Hilmi Aprilia; Aziz, Muhammad Ilham (Indonesian Journal Publisher, 2023)
This research examines the philosophy of history from the perspective of Saint Augustine. Saint Augustine has contributed to the field of philosophy, and became one of the philosophers of speculative history. Meanwhile, the aim is to see historical thoughts and historical movements from Saint Augustine. This research can be classified in philosophical research. The method used in this study is a qualitative method with literature review as a research reference source. While data analysis techniques, the authors use Miles and Huberman which starts from data reduction, presentation, and conclusions. The results of this study indicate that Saint Augustine was an influential figure in the Middle Ages, Saint Augustine's thought was influenced by the teachings of Manichaenism and Neo Platonism. He argues that history is an event that is not determined by humans, but is determined by God. Meanwhile, according to him, the movement of history is regulated by God. He believes that the movement of history is linear, ending and ending in the kingdom of God.